Duality for smooth families in equivariant stable homotopy theory - Hu po (Paris Societe Mathematique De France, 2003)
In this paper, we formulate and prove a duality theorem for the equivariant stable homotopy category, using the language of Verdier duality from sheaf theory. We work with the category of G-equivariant spectra (for a compact Lie group G) parametrized ove
Keywords: Homotopy theory; Isomorphisms; Sheaf theory